2009
DOI: 10.1242/jeb.024125
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporins: translating bench research to human disease

Abstract: SummaryThere is considerable potential for translating knowledge of aquaporin structure, function and physiology to the clinic. One area is in aquaporin-based diagnostics. The discovery of AQP4 autoantibodies as a marker of the neuromyelitis optica form of multiple sclerosis has allowed precise diagnosis of this disease. Other aquaporin-based diagnostics are possible. Another area is in aquaporin-based genetics. Genetic diseases caused by loss-of-function mutations in aquaporins include nephrogenic diabetes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
87
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(89 citation statements)
references
References 102 publications
(86 reference statements)
1
87
0
1
Order By: Relevance
“…Similarly to AQP0, it has also been reported that each AQP4 tetramer interacts with four tetramers in the opposing membrane (29). Although the pathophysiological significance of this structure of AQP4 is still not clear (30), it is suggested that the structure mediates AQP4-dependent adhesion. We do not know whether this is the case for AQP11, but it is considered that the correct tertiary and/or quaternary structure of AQP11 is necessary for a structural role of the molecule inside or/and outside cells and that this role may be important for the function of hAQP11 in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to AQP0, it has also been reported that each AQP4 tetramer interacts with four tetramers in the opposing membrane (29). Although the pathophysiological significance of this structure of AQP4 is still not clear (30), it is suggested that the structure mediates AQP4-dependent adhesion. We do not know whether this is the case for AQP11, but it is considered that the correct tertiary and/or quaternary structure of AQP11 is necessary for a structural role of the molecule inside or/and outside cells and that this role may be important for the function of hAQP11 in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…AQP4 is the predominant water channel in the brain and has a significant role in the pathophysiology of brain edema. [32][33][34][35][36] Evidence suggests V1aR regulate the expression and function of AQP4, 17,22,37 although the mechanism is still elusive. 17,22,[29][30][31] Recently, we explored the hypothesis that selective V1aR inhibition by the non-peptide antagonist SR49059 30,38 can reduce brain edema in animal models of middle cerebral artery occlusion 22,39 and TBI.…”
Section: Introductionmentioning
confidence: 99%
“…2 AQPs are classified, according to their sequence homology and permeability, into three subfamilies: (i) the water-specific "classical" AQPs, (ii) the aquaglyceroporins, and (iii) the unorthodox AQPs. 4 , [8][9][10][11] The aquaglyceroporin subfamily transports glycerol in addition to water because of the presence of an aspartic residue near the second NPA box, resulting in expansion of the pore to accept a larger molecule such as glycerol. The four subtypes of the aquaglyceroporin subfamily are: AQP3, AQP7, AQP9, and AQP10 (reviewed in refs.…”
Section: Introductionmentioning
confidence: 99%